Effects of Dietary Resveratrol and Black Soldier Fly (Hermetia illucens) Larvae Meal Supplements on Quail Egg Production, Quality, and Consumer Acceptance - Violeta Razmaitė; Artūras Šiukščius; Vidmantas Pileckas; Saulius Bliznikas (Animals)
This study aimed to examine the effects of supplementing a basal diet with resveratrol and black soldier fly (Hermetiaillucens) larvae meal on Manchurian Golden quail egg production and quality as well as consumer attitudes towards the quail eggs and their acceptability. Quail were allotted three treatments for a laying period of 3 months. The dietary treatment groups were those of a basal diet, a basal diet with 250 mg/kg resveratrol pliusACE, and a diet supplemented with 10% black soldier fly larvae meal (BSF). The BSF larvae meal supplement increased the live weight of the quail, but the differences in the mean egg production and egg external parameters between the experimental groups were insignificant. The egg yolk from the quail fed with resveratrol and BSF supplementation demonstrated lower (p < 0.001 and p < 0.01) pH compared with the quail fed a basal diet. Egg yolk colour showed lower (p < 0.05) lightness and lower (p < 0.01) yellowness and colour saturation in the group of quail fed with resveratrol supplement compared with BSF supplement. Resveratrol inclusion in the basal diet resulted in increased (p < 0.001) protein content in the yolk. BSF inclusion in the diet showed the effect by increasing (p < 0.001) dry matter in albumen. The total monounsaturated fatty acids, polyunsaturated fatty acids, and cholesterol content were not affected by the dietary treatment. The inclusion of BSF larvae meal in the diet increased the proportion of total saturated fatty acids and lowered the proportion of total trans fatty acids in yolk lipids and demonstrated less favourable ratios of fatty acids and nutritional indices, except for the peroxidisability index, and showed higher oxidative status (p < 0.05), flavour score, and overall egg acceptance compared with the quail fed on a basal diet.